Training of Natural Science Learning based Ethno-STEM for Teacher of Muhammadiyah Secondary School in Sidoarjo - Septi Budi Sartika; Fitria Eka Wulandari; Luluk Iffatur Rocmah; Nur Efendi (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
Local wisdom that was raised as a model to understand the concept of natural science has been done in various regions and improved good results. In the current condition of the covid-19 pandemic, natural science teachers need effective learning strategies in conveying concepts, through natural science learning based ethno-STEM this can be answered. The community servicer was gathered natural science teachers of SMP Muhammadiyah throughout Sidoarjo regency to develop natural science learning based ethno-STEM what material and instruments through training. This activity was attended by 21 natural science teachers, representing of ten SMP Muhammadiyah throughout Sidoarjo regency. The activity lasted for 4 days from December 30, 2020 to January 2, 2021, which produced natural science learning based ethno-STEM what material and instruments for secondary school grade VII, VIII, and IX even semester. These learning material and instruments have also been studied by experts so that the results of improvements will improve the validity of the devices and instruments in question. The resulting devices and instruments will be compiled and made into practical books teaching natural science based ethno-STEM. This book is then registered in the Library of The Republic of Indonesia and registered in the Intellectual Property Rights. Advice for further community service activities so that devices and instruments can be implemented in students so that their practicality and effectiveness are tested.